ANALISIS PENGARUH INFLASI, UPAH MINIMUM, DAN ANGKA HARAPAN HIDUP TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KABUPATEN/KOTA PROVINSI BANTEN TAHUN 2008-2020 - Novella Luckytha Putri; Muljaningsih, Sri (Journal of Development Economic and Social Studies, 2023)
One of the problems that often occurs in developing countries is the high rate of open unemployment, this can be caused by several factors, including due to the fact that the wages provided are not able to attract the interest of the workforce to work in the formal sector, as well as the impact of poor health levels resulting in inadequate optimal effort given by HR in work. In addition to these two factors, too high inflation also had an impact on hampering the absorption of the labor force. Therefore, one of the policies implemented by the Banten provincial government is to gradually increase the minimum wage to increase the interest of the workforce so they can work in the formal sector. This study aims to determine the effect of inflation, minimum wages and life expectancy on the open unemployment rate in districts/cities, Banten Province in 2008-2020. The method used in this study is a quantitative approach using secondary data in the form of district/city panel power in Banten Province in 2008-2020, to be further analyzed using panel regression through the Eviews application version 9. The results in this study indicate that inflation has a negative effect but not significant to the open unemployment rate, the minimum wage has a negative and significant effect on the open unemployment rate and life expectancy has a negative and significant effect on the open unemployment rate and inflation, the minimum wage and life expectancy have a significant effect simultaneously or together - the same as the open unemployment rate in the Regency/City of Banten Province.